A Phenomenological Analysis of Youth Who Prefer Hanging Out over Performing Congregational Prayer at the Mosque: Factors, Motivations, and Developmental Solutions. - Sharhan Asad Almawarid; Rahmad Padilah; M. Fadhli; Rodi Wahyudi (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
The social phenomenon of young people preferring to hang out in entertainment venue such as cafes, malls, or shopping centers rather than performing congregational prayers at the mosque has become both a religious and social issue that requires serious attention.This study aims to analyze the factors contributing to the low interest of youth in enlivening the mosque, to understand why youth-friendly mosques with modern facilities remain quiet while simple mosques are instead filled with young worshippers, and to formulate appropriate guidance strategies to revive the spirit of congregational prayer among the youth. This study employs a qualitative research method with a phenomenological approach. The type of research applied is a mixed research method, combining library research and field research. The data were collected through literature review, observation, interviews, questionnaires, surveys, and documentation related to youth behavior and the condition of mosques in several locations in the city of Pekanbaru. The findings indicate that peer environment, modern lifestyle, and the lack of family guidance and religious leadership are the main factors behind the declining presence of youth in mosques. However, mosques that succeed in building emotional bonds, providing exemplary religious figures, and strengthening community culture remain vibrant even without complete facilities.. The study concludes that strategies for fostering youth engagement in mosque activities should emphasize the synergy among families, mosque management, and the community through spiritual, educational, and social approaches that can attract young people to consistently perform congregational prayers.